Recent advances in nanostructured Sn−Ln mixed-metal oxides as sunlight-activated nanophotocatalyst for high-efficient removal of environmental pollutants. Issue 17 (1st September 2021) - Zinatloo-Ajabshir, Sahar; Mousavi-Kamazani, Mehdi
Abstract: Environmental contaminants are toxic and undesirable compounds that can endanger the health and survivorship of human society. Thus, their removal from the environment has become a hot subject of research. Photocatalysis is accepted as a beneficial and environmentally friendly solution for the removal of undesirable contaminants. Its most substantial advantage is the capability to mineralize a wide variety of contaminants. Among various nanoscale compounds, mixed-metal oxides of tin (Sn) and lanthanide (Ln) with unique features and high reactivity have been demonstrated to be promising photocatalysts for removing undesirable contaminants. This review is aimed to give a comprehensive overview of current research progress concerning solar photocatalytic applications utilizing mixed-metal oxides of tin (Sn) and lanthanide (Ln). Diverse techniques for fabrication of mixed-metal oxides of tin (Sn) and lanthanide (Ln) and comprehensive experimental outcomes revealing their application in solar photocatalysis for removing undesirable pollutants are summarized. Besides, factors influencing the solar photocatalytic process have been briefly discussed. Ultimately, inspiring outlooks on this area of research are offered with the purpose of prevailing challenges.